Bakteriosin dari Bakteri Asam Laktat sebagai Biopreservasi pada Daging dan Olahan: Tinjauan Potensi Hingga Industrinya - Diannisa Syahwa Rahma Fadila; Jilan Hasanati; Amalia Sekar Kusumawardhani; Muhammad Fathur Rachman; Muhammad Afi Naufal; Farhan Wahyu Febrian; Megga Pikoli; Irawan Sugoro (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2022)
The use of bacteriocin as biopreservation agent is an important alternative strategy to maintain the safety and quality of meat and meat products. The increasing consumer concerns about the quality and safety of food from chemical additives have led to the development of studies on the use of bacteria and their metabolites as natural antimicrobials that have the potential to extend shelf life and improve food safety. This article aims to systematically review knowledge regarding the use of bacteriocin-producing lactic acid bacteria and their production on an industrial scale as a natural preservative in meat and its products. The results of several studies prove the potential of lactic acid bacteria and metabolites as biopreservatives in meat and processed meat products with several conditions that must be considered to achieve a longer shelf life and inhibit the spoilage of pathogenic bacteria. The use of bacteriocins from lactic acid has obstacles as well as advantages. However, these barriers can be overcome by reducing the level of purification protocols required, or by using food grade media such as dairy and food industrial waste products to produce bacteriocins. The potential and production of bactetriocins on an industrial scale are discussed.